Detecting Interdecadal Change in Western North Pacific Tropical Cyclone Genesis Based on Cluster Analysis Using pHash + Kmeans - Tian, Ye; Zhou, Wen; Wong, W. K. (Frontiers in Earth Science, 2022)
Previous studies have noted an abrupt decrease in western North Pacific (WNP) tropical cyclone (TC) genesis frequency and a westward shift in genesis location since the late 1990s. The recent application of cluster analysis in TC research shows the effect of detecting the contribution of the Western North Pacific Subtropical High (WNPSH) and the interdecadal Pacific oscillation (IPO) on interdecadal change in WNP TCs. In this work, we also apply a clustering algorithm called pHash + Kmeans to group WNP TCs into three classes based on their genesis environmental conditions. The clustering results show that an abrupt decrease after 1998 is related primarily to a decrease in the dominant class (Class3, located mainly in the southern and eastern WNP), and an increase after 2010 occurs because of a new dominant class (Class1, located mainly in the northwestern WNP), which indicates that the WNP environment suppresses Class3 genesis after 1998 and enhances Class1 genesis after 2010. Three periods (P1: 1979–1997, P2: 1998–2010, and P3: 2011–2020) and three regions (SCS: 100°E-120°E, EQ-30°N; WNP1: 120°E-140°E, EQ-30°N; and WNP2: 140°E-160°W, EQ-30°N) are divided to further confirm the above findings. In P1, high (low) mid-level relative humidity (RH), intense (weak) low-level vorticity, and weak (strong) vertical wind shear (VWS) are distributed in WNP2 (SCS and WNP1), indicating suitable environmental conditions for TC genesis in WNP2 but unsuitable conditions in SCS and WNP1. This situation is the opposite in P2, leading to a decrease in genesis frequency and a westward shift in genesis location. In P3, strong low-pressure vorticity and thermodynamic conditions occur in SCS and WNP1, contributing to an increase in TC genesis frequency.